Investigation of sorption isotherms of wheat germ for its effect on lipid oxidation. Issue 5 (12th April 2022) - Koç, Andaç; Erbaş, Mustafa
Abstract: This research aimed to investigate the oxidation and sorption isotherm properties of wheat germ and to determine monolayer moisture content ( m 0 ) in particular, because it has a limiting effect on lipid oxidation. This research comprised two stages. The first stage was the determination of sorption properties and m 0 at three temperatures (15, 25, and 35°C). The second stage of the research was to investigate lipid oxidation properties of stored wheat germ at two different temperatures (4 and 25°C) and m 0 for 28 days. As a result, it was determined that wheat germ has a Type II sorption isotherm, Halsey is the best fitting sorption equation, and the average m 0 is 4.25 g moisture per 100 g dry matter. Furthermore, the free fatty acid and peroxide value of wheat germ oil increased with increasing storage moisture content and temperature, determined as 12.63% and 5.01 mEqO2 /kg on average, respectively. In conclusion, storage of impermeably packaged wheat germ at low temperature and m 0 content is an applicable method for decreasing rancidity and prolonging shelf‐life.